2019
DOI: 10.11113/jt.v81.13613
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediaton of Heavy Metals From Wastewater by Constructed Wetland Microcosm Planted With Alocasia Puber

Abstract: Water pollution by toxic heavy metals is a global environmental problem. It has led to the development of alternative technologies for heavy metals removal from contaminated sites. Constructed wetland microcosm by using Alocasia puber is a possible treatment method for wastewater containing heavy metals. Synthetic wastewater with heavy metals Cd, Cr, Cu, Ni, and Zn were used in this study. Several heavy metals concentrations (5 mg/L, 10 mg/L and 100 mg/L) were used in the systems. Six different hydraulic reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Among these pollutants, metals are particularly dangerous because of their non-degradable nature (Muhammad et al 2009); bioaccumulation in the environment and throughout the trophic chain; and potential harm to aquatic organisms chronically or acutely (Gall et al 2015). Most conventional techniques relying on chemical and physical steps are yet costly and environmentally unsafe (Olguín and Sánchez-Galván 2012;Martín-Lara et al 2014), which requires eco-technologies advancement (Thani et al 2019). Thus, effective, economically, and ecologically attainable treatments are desirable to prevent metals from entering water bodies (Shahid et al 2018), which can deplete water quality and threat aquatic ecosystems' health (Mânzatu et al 2015;Wacławek et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among these pollutants, metals are particularly dangerous because of their non-degradable nature (Muhammad et al 2009); bioaccumulation in the environment and throughout the trophic chain; and potential harm to aquatic organisms chronically or acutely (Gall et al 2015). Most conventional techniques relying on chemical and physical steps are yet costly and environmentally unsafe (Olguín and Sánchez-Galván 2012;Martín-Lara et al 2014), which requires eco-technologies advancement (Thani et al 2019). Thus, effective, economically, and ecologically attainable treatments are desirable to prevent metals from entering water bodies (Shahid et al 2018), which can deplete water quality and threat aquatic ecosystems' health (Mânzatu et al 2015;Wacławek et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mohamad Thani et al. (2019) investigated the removal of 5−100 mg/L HMs (cadmium, copper, chromium (Cr), nickel (Ni), and zinc) using a vertical‐flow CW without water recirculation where soil and gravel were filled and Alocasia macrorrhiza was planted. They found that the HM removal efficiency varied depending on the influent HM concentration and HRT: HRT of 6 days or longer was required for >90% removal of 10 mg/L HMs, and the removal of some HMs at 100 mg/L was low even when the HRT was extended to 12 days.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to maximise the removal efficiency of Ni from water using response surface methodology (RSM) through a central composite design (CCD), by optimising heavy metal concentration and exposure time. Among all of the preliminary experiments conducted on heavy metals (including Cr, Cd, Ni, Cu, and Zn), Ni was selected as a potential heavy metal to be removed using the CW systems, due to its maximum removal potential, as reported in a previous study by Mohamad Thani et al [25].…”
Section: Introductionmentioning
confidence: 99%